Evidence-based practice in exercise science the six-step approach - Amonette, William E. 1977-; English, Kirk L. 1975-; Kraemer, William J. 1953- (Human Kinetics, 2016)
"Evidence-Based Practice in Exercise Science: The Six-Step Approach equips readers with the basic skills and competencies for discerning the value of scientific research. Using a methodical approach, students and professionals will learn to identify appropriate evidence to support novel interventions and avoid counterproductive or dangerous information to eliminate ineffective exercise options. This text is an instruction manual in understanding and applying evidence-based practice. The process is divided into six steps that begin with asking a question and then finding, evaluating, implementing, confirming, and re-evaluating the evidence."--Back cover